Single-Center Experience With Endovascular Treatment for Splenic Artery Aneurysms in Long-Term Follow-Up: A Retrospective Study - Cao, Yanyan; Song, Songlin; Ouyang, Tao; Zheng, Chuansheng (Frontiers in Cardiovascular Medicine, 2022)
Objectives: To reveal a single-center experience with endovascular treatment for splenic artery aneurysm (SAA) and analyze the safety and efficacy of the operation in the long-term follow-up. Materials and methods: A total of 49 patients with SAAs (21 males, 28 females; mean age, 52.4 y ± 11.5) were enrolled in the study rom July 2010 to December 2020. Baseline and SAAs’ characteristics were collected. Parent artery coil embolization or combined with sac coil embolization of SAAs, graft-stent implantation or bare-stent-assisted coil embolization were performed to for the treatment of SAAs. Adverse events and follow-up data were recorded. Results: The average diameter of SAAs was 3.3 ± 2.5 cm (range, 1.0-13.6 cm). An individual-tailed modality was conducted for three patients. A 100% technical successful rate was achieved. No re-intervention procedure was performed in all patients. No major treatment-related adverse events were observed, and no expansion or rupture of SAAs occurred in in the average follow-up period of 57.9 ± 27.3 months (19-125 months). Conclusions: Endovascular treatment of SAA, including the individual-tailed therapy for three cases, is safe, effective and minimally invasive with high technical success rates and satisfactory outcomes during the long-term follow-up period.